2011
DOI: 10.1002/adfm.201100344
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Electrochemical Biosensing Platform by Employing Conductive Nanocomposite Entrapping Magnetic Nanoparticles and Oxidase in Mesoporous Carbon Foam

Abstract: A conductive multi‐catalyst system consisting of Fe3O4 magnetic nanoparticles (MNPs) and oxidative enzymes co‐entrapped in the pores of mesoporous carbon is developed as an efficient and robust electrochemical biosensing platform. The construction of the nanocomposite begins with the incorporation of MNPs by impregnating Fe(NO3)3 on a wall of mesoporous carbon followed by heat treatment under an Ar/H2 atmosphere, which results in the formation of magnetic mesoporous carbon (MMC). Glucose oxidase (GOx) is subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Among them nanoparticle (NP) based catalysts have attracted increasing interest. Up to now, various NPs made of metals, metal oxides, and carbons have been reported to resemble the functions of various enzymes‐like oxidase, peroxidase, catalase, and superoxide dismutase . Recent studies revealed that activities of NPs are greatly dependent on the particle size, shape, and surface facets, which could be affected by charges, coatings, dopings, loadings, and external fields.…”
Section: The Structure Of Nanozymesmentioning
confidence: 99%
“…Among them nanoparticle (NP) based catalysts have attracted increasing interest. Up to now, various NPs made of metals, metal oxides, and carbons have been reported to resemble the functions of various enzymes‐like oxidase, peroxidase, catalase, and superoxide dismutase . Recent studies revealed that activities of NPs are greatly dependent on the particle size, shape, and surface facets, which could be affected by charges, coatings, dopings, loadings, and external fields.…”
Section: The Structure Of Nanozymesmentioning
confidence: 99%
“…10, 15 MNP are promising nanocatalysts because of their magnetic properties, high catalytic activity, and adjustability through nanoscale modifications 10, 1619 , suggesting possible uses in immunoassays 10, 13, 20, 21 , organic pollutant degradation 12, 2226 , glucose detection 17, 18, 2731 and cancer diagnostics. 14 Although it has been reported that MNP alone or combined with H 2 O 2 can prevent biofilm formation by inhibiting bacterial growth, 32, 33 there are no reports regarding the efficacy of an MNP-H 2 O 2 system on biofilm destruction and killing of bacteria resident within biofilms—a much more difficult medical challenge.…”
mentioning
confidence: 99%
“…There have been several reports of an electrochemical biosensing platform using GOx-coupled nanozymes. A highly efficient and robust electrochemical biosensing strategy employing a nanocomposite harboring GOx-coupled nanozymes was developed by our group [49]. In this report, MNPs and GOx were entrapped in the pores of mesoporous carbon, in which GOx immobilized in the nanocomposite generates H 2 O 2 which then is directly reduced to H 2 O, with the electrocatalytic reduction mediated by MNPs.…”
Section: Glucose Detectionmentioning
confidence: 99%